7 steps to an award-winning school library program [ - Martin, Ann M. (Santa Barbara, California : Libraries Unlimited, 2012)
Accomplishing positive change is challenging in today's educational environment, even when efforts are guided by best practices and desperately needed. In fact, librarians who are put in the position of acting as change agents are often stymied as segments of the learning community push back against the introduction of new resources, technologies, and program initiatives. How can the barriers to change be overcome so that a library program can be transformed?
1. Creating a team -- 2. Getting started -- 3. Analyzing the results -- 4. Identifying and overcoming Barriers -- 5. Developing trainingmodules -- 6. Building advocacy plans -- 7. Applying for an award
Rev. ed. of: 7 steps to an award-winning school library program. 2005
Includes bibliographical references and index
Keywords: Library planning -- United States; School libraries -- Awards -- United States; School libraries -- Evaluation; School libraries -- United States